Factors influencing adherence to standard and contact precautionary measures in care for critical patients: Integrative review (Research, Society and Development, 2021)
Objective: To identify, in the scientific literature, the factors that influence the adherence to standard and contact precautionary measures by health professionals during the care of critical patients. Methodology: This is an integrative literature review, based on scientific investigations published between 2015 to 2020. Searches were carried out in databases: Foram efetuadas buscas nas bases de dados: BDENF, LILACS, MEDLINE, PUBMED and SCIELO, using the descriptors: Universal Precautions; Intensive Care Units; and, Infection Control. Results: 1,522 publications were identified, of which 10 met the established eligibility criteria. From the results, it was identified that the low adherence to standard and contact precautions may be related to the individual factors of the professionals, the deficiency in training, the organizational structure of the institution, the management of the unit and the working conditions. Final Considerations: The rates of adherence to standard and contact precautionary measures by health professionals working in the Intensive Care Units are still below expectations, whether in terms of hand hygiene, handling and disposal of sharps or use of personal protective equipment.